Development of 3D printable cementitious composite for electromagnetic interference shielding. (24th January 2022) - Wanasinghe, Dimuthu; Aslani, Farhad; Ma, Guowei
Highlights: 3D printed specimens showed better mechanical properties. Optimal level of EMI shielding for 3D printed specimens was 43.61 dB. Fibre alignment on the direction of printing affected conductivity and shielding. 3D printed specimens showed less porosity and longitudinal fibre arrangement. ACP reduced the EMI SE by distorting the CF network in 3D printed specimens. Abstract: Interference caused by electromagnetic radiation is a common reason for the malfunction of many sensitive electronic devices, which has a significant impact in areas such as defence and medical instrumentation. This research aims to fabricate a cementitious mix that could be used to prevent electromagnetic interference (EMI) and also be 3D printed so that required structures could be fabricated in a short amount of time. Additives with high electrical conductivity were mixed in different percentages to an established control mix to impart EMI shielding properties. To observe the effect of 3D printing, cast specimens with the same mix design were fabricated and tested after 28 days in conditions identical to the 3D printed specimens. EMI shielding properties were measured in accordance with ASTM D4935 – 18 standard to ensure results from this research can be compared with similar research that utilised the same standard. Results revealed that 3D printed specimens had better mechanical properties than cast specimens. EMI shielding properties of 3D printed specimens with 3 mm carbon fibres had better overall shielding properties than the cast specimens. In specimens with 12 mm carbon fibre, cast specimens showed better properties when the fibre content was low but the properties were similar to those of the printed ones when the fibre content was increased. 3D printed specimens with 0.7 % of 12 mm carbon fibre showed an average EMI shielding effectiveness (SE) of 43.61 dB within the 30 MHz to 1.5 GHz frequency range. Activated carbon powder was used in conjunction with carbon fibre to improve the EMI shielding properties. However, activated carbon powder failed to yield expected results and produced specimens with lower SE. Scanning electron microscope images revealed that carbon fibres are oriented in the direction of printing in 3D printed specimens and they have a lower amount of porosity compared to cast specimens.